'Flower-like' micropillars of copper with porous nanowalls as effective hydrophobic surface. (April 2013) - Tian, C F; Zhang, F L; Cai, H H; Fang, J X; Ding, B J
Abstract : The wetting properties of porous Cu nanowall arrays prepared by a facile replacement reaction are reported. The influences of various experimental parameters including the concentrations of Cu ions and reaction time on final products were investigated. It was found that a hierarchical structure containing micro- and nanoscale structure can be formed on zinc substrate. The measurements of water contact angle indicated that the hydrophobic nature of the hierarchical nanostructures can be tuned by reaction times. When reaction time reached 5 min, its wettability switched from hydrophilic to hydrophobic with a contact angle of >120°. By using modified Cassie–Baxter models, we investigated the relation between hierarchical structure and hydrophobic property. Moreover, Cu flower-like hierarchical nanostructures exhibits good hydrophobic properties.